Requirements for building educational and care technology on heart failure - Virna Ribeiro Feitosa Cestari; Raquel Sampaio Florêncio; Thiago Santos Garces; Lorena Campos de Souza; Jéssica Naiane Gama da Silva; Vera Lúcia Mendes de Paula Pessoa; Thereza Maria Magalhães Moreira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to investigate the requirements for building an educational and care application about heart failure. Methods: exploratory study, carried out with 15 people with heart failure and 19 family members/caregivers, assisted in a tertiary unit in the Brazilian Northeast. Individual semi-structured interviews were carried out between November and December 2020. Hannah Arendt's theoretical framework was adopted. Results: two units of meaning emerged: "The plurality of care in heart failure" and "Expectations on the construction and use of educational and care technology for heart failure". The requirements involved the need to know the disease and its nuances, as well as the health network, through an application that can minimize individual and social precariousness; and highlighted the importance of the participation of the multidisciplinary team in the development and dissemination of the application. Conclusions: requirements on educational and care technology were identified and will support the creation of an application that promotes care, aiming to obtain positive health outcomes.